The Effect of Problem-Based Approach Assisted with Mobile Augmented Reality toward Students’ Science Process Skills And Achievement - Yuliana Wahyu; Kanisius Supardi; Marlinda Mulu; Yosef Firman Narut (IKIP Mataram, 2021)
Problem Based Learning (PBL) is a student-oriented approach. PBL is a student-centered approach that can answer 21t century educational challenges. This research approach applies the PBL approach assisted by Mobile Augmented Reality (MAR) as a technology-based media that combines the virtual world with the real world to science process skills and achievement. The purpose of the study was to investigate the effect of the PBL approach assisted with MAR on the learning process skills and outcomes of the students at the Primary Education Teacher Program of Universitas Katolik Indonesia (UNIKA) St. Paulus Ruteng. The research design used was a pretest/posttest control group design with a one-way MANOVA statistical test. Based on the results of hypothesis testing (F test) shows that 1) there is a significant difference in the science process skills of students who take learning with the MAR-assisted PBL model and students who take conventional learning; 2) there is a significant difference in the learning outcomes of students who take learning with the PBL model assisted by MAR and students who take conventional learning; 3) there is a significant difference in the skill process and science learning outcomes of students who take learning with the MAR-assisted PBL model and students who take conventional learning.